Final Year Medical Students' Perception of Different Assessment Methods in the Internal Medicine Department, University of Benghazi - Najat Buzaid; Sami A Lawgaly (Benghazi University Medical Journal, 2026)
Introduction: Assessment of medical students involves many challenges and processes to develop competent physicians; nonetheless, students' feelings and perceptions of assessment methods are usually neglected. Aim: To evaluate the perception of final year medical students to different assessment methods in the final examination at the Department of Internal Medicine, Faculty of Medicine, University of Benghazi. Methods: A cross-sectional study. An electronic three-point Likert scale questionnaire was distributed to final year medical students electronically. Results: A total number of 337 students were included in the study. The majority of the studied group were females and accounted for 255 (75.7%). The mean age was 27.7 years. Exam unfairness was reported by 85.8% of students while 81.9% reported that the exam was dreadful. Females significantly reported more perception of exam unfairness than males 90%vs 74% respectively (P=0.0013). Conclusion: Students reported high anxiety, and females perceived unfairness more significantly than males.